2013
DOI: 10.1590/0103-6440201302263
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Composite Resins Subjected to Accelerated Artificial Aging

Abstract: The aim of this study was to investigate the influence of accelerated artificial aging (AAA) on the microstructure and mechanical properties of the Filtek Z250, Filtek Supreme, 4 Seasons, Herculite, P60, Tetric Ceram, Charisma and Filtek Z100. composite resins. The composites were characterized by Fourier-transform Infrared spectroscopy (FTIR) and thermal analyses (Differential Scanning Calorimetry -DSC and Thermogravimetry -TG). The microstructure of the materials was examined by scanning electron microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…That may be explained to some extent by the various methods, which differ in the duration for one cycle and the temperature or the storing medium. Some authors determined a slight decrease [26, 29] while others found a slight increase in strength [2729]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That may be explained to some extent by the various methods, which differ in the duration for one cycle and the temperature or the storing medium. Some authors determined a slight decrease [26, 29] while others found a slight increase in strength [2729]. …”
Section: Discussionmentioning
confidence: 99%
“…In various studies it has been demonstrated that hardness of composite filling materials is not affected by thermal cycling, while flexural strength decreases significantly under the same conditions [2629]. In contrast to these findings Medeiros et al [24] report on a positive correlation between Vickers hardness and indirect tensile strength when investigating the aging of a composite resin restorative material, while Aguiar et al [25] observed the opposite.…”
Section: Introductionmentioning
confidence: 99%
“…The aging is dependent upon many factors and can promote alterations in the surface microstructure, the chemical composition of the matrix, and filler particles of composite resins (DOS REIS et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These results corroborate with Catelan et al, 14 who analyzed the Vit-l-escence composite resin and observed a reduction in surface microhardness after AAA. However, in a study performed by Reis et al 15 demonstrated that AAA did not change the mechanical and physical properties, such as hardness, compressive strength, thermal behavior, and spectral profile, of Tetric N-Ceram. It is important highlighted that study used a 50 kgf load for 5 seconds, which was different from the study conducted by Catelan et al 14 and the present study which used equivalent parameters, 50 kgf load for 15 seconds and a 25 kgf load for 30 seconds, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…It is important highlighted that study used a 50 kgf load for 5 seconds, which was different from the study conducted by Catelan et al 14 and the present study which used equivalent parameters, 50 kgf load for 15 seconds and a 25 kgf load for 30 seconds, respectively. 14,15 Various methods can be used to assess colors, such as the use of guide scales, image analysis, colorimeters, or spectrophotometers. Since the use of spectrophotometers allows for objective assessment and provides accurate quantitative data, it was the method utilized in this study.…”
Section: Discussionmentioning
confidence: 99%